Geochronology and geochemistry of early Palaeozoic intrusive rocks in the Lajishan area of the eastern south Qilian Belt, Tibetan Plateau: Implications for the tectonic evolution of South Qilian. (15th October 2018) - Cui, Jiawei; Tian, Liming; Sun, Junyi; Yang, Chao
Abstract : The Lajishan area, located in the South Qilian orogenic Belt, north‐eastern Tibetan Plateau, contains a compositionally diverse range of Cambrian to early Ordovician felsic intrusions that reflect the early Palaeozoic tectonic evolution of the Central Qilian Belt. This paper presents new geochemical, Sr─Nd and Lu─Hf isotopic, and zircon U─Pb data for the Tadong, Huangcaoshan, and Yindonggou plutons in the eastern Lajishan area. LA‐ICPMS U─Pb ages of 517.4 ± 1 Ma for the Tadong pluton which is the first find Late Cambrian granitoids in this area, 467 ± 1 Ma for the Huangcaoshan pluton and 446 ± 1 Ma for the Yindonggou pluton. The new data indicate that the Tadong pluton and Huangcaoshan pluton belong to I‐type granite. Their A/CNK values range from 0.82 to 1.03, suggesting a close relationship with I‐type granitoids. Their trace‐element geochemical characteristics include enrichments in the LILEs, pronounced depletions in Nb and Ta, enrichment of the LREEs relative to the HREEs, and Eu anomalies. These features are similar to those of I‐type volcanic‐arc magmas. Combined with Hf and Sr─Nd isotopic data, The Tadong pluton generated by the mixing of melts was derived from the partial melting of the Precambrian basement and mantle‐derived magmas. The Huangcaoshan pluton was derived from juvenile crust with contamination. The Yindonggou pluton shows A‐type characteristics, their A/NCK is 0.88–1.07, and 10000 × Ga/Al is higher than 2.6. They were characteristic with high Sr, low Y, low Yb, and enriched LREE. Combined with Hf and Sr─Nd isotopic data, the Yindonggou pluton was generated by the partial melting of oceanic slab material and was crustally contaminated associated with slab breakoff. Combined previous research suggests that Tadong pluton and Huangcaoshan pluton formed from southern subduction of the South Qilian ocean into the Central Qilian Belt; the Yindonggou pluton formed in collisional setting.